Natural convection in a hydrodynamically and thermally anisotropic non-rectangular porous cavity: effect of internal heat generation/absorption - Chandran, Pallath; Sacheti, Nirmal C.; Bhadauria, Beer Singh; Singh, Ashok Kumar (Zielona Góra: Uniwersytet Zielonogórski)
Laminar natural convection in a trapezoidal porous vertical cavity has been investigated in this work. It is assumed that the porous enclosure is filled up with a permeable material subject to hydrodynamic and thermal anisotropy, the flow being governed by the Darcy law as applicable to a non-isotropic medium. It is further assumed that (i) there is heating at the left vertical wall and cooling at the right wall of the enclosure and (ii) the flow domain is subject to the presence of heat source or heat sink.
Keywords: natural convection; trapezoidal cavity; porous medium; permeability; thermal diffusivity; Darcy law; heat source/sink